Fine-scale drivers of African Penguin prey dynamics in Algoa Bay, South Africa, and their impacts on penguin foraging ecology - Mcinnes, Alistair McIntyre (Percy FitzPatrick Institute of African Ornithology, 2017)
African Penguins (Spheniscus demersus) have undergone a dramatic decrease in their population since the turn of this century prompting the up-grading of their conservation status to 'endangered'. There is growing evidence that variation in the availability of their principle prey, pelagic shoaling fish, are driving this trend. This prey variability is driven by oceanographic factors as well as commercial purse-seine fishing operations. To isolate the direct impacts of fishing on the foraging performance of African Penguins, the primary oceanographic drivers of fish distribution and abundance were investigated by conducting fine-scale pelagic fish surveys around two of the largest breeding colonies of African Penguins in Algoa Bay, St Croix and Bird islands, between 2011 and 2014. Quantification of fish parameters were facilitated by a novel method using a recreational fishfinder and calibrating this instrument to a conventional scientific device. The specific types of fish assemblages selected for by African Penguins were then evaluated by looking at the correspondence in associations of fish and penguins recorded at sea using both counts and locations of foraging birds tracked simultaneously during a subset of fish surveys. Activity budgets of penguins calculated from these simultaneous deployments were modelled against the abundance of their prey to elucidate hypothesised functional relationships. Finally, the direct influence of purse-seine fishing on both targeted fish assemblages and penguin activity budgets were assessed by modelling interactions between known physical drivers of targeted fish assemblages and different levels of cumulative catches. Physical drivers of the three-dimensional distribution and abundance of fish varied between colonies with primary production playing the most important role around Bird Island but having little influence on fish around St Croix Island where factors associated with surface and sea-profile temperatures had a stronger influence. Results of both penguin count and track data highlight the importance of the vertical distribution of prey to the distribution of foraging African Penguins with the abundance of these assemblages having a significant influence on this species' activity budgets. Evidence for local depletion of pelagic fish was demonstrated for the waters around St Croix Island and the effects of purse-seine fishing on African Penguin foraging effort were significant when controlling for natural drivers of prey distribution. Results of this research should be applied to current conservation measures, most notably alleviating direct competition by purse-seine fishing operations during periods of reduced primary productivity and when the abundance of targeted fish aggregations are significantly diminished three months prior to and during the onset of the African Penguin breeding season.